Upregulation of ATP6V0D2 benefits intracellular survival of Leishmania donovani in erythrocytes-engulfing macrophages - Hong, Jing; Mukherjee, Budhaditya; Sanjoba, Chizu; Yamagishi, Junya; Goto, Yasuyuki (Frontiers in Cellular and Infection Microbiology, 2024)
Visceral leishmaniasis (VL) is the most severe type of leishmaniasis which is caused by infection of Leishmania donovani complex. In the BALB/c mouse model of VL, multinucleated giant cells (MGCs) with heavy parasite infection consist of the largest population of hemophagocytes in the spleen of L. donovani-infected mice, indicating that MGCs provide the parasites a circumstance beneficial for their survival. Although ATP6V0D2 is a demonstrated factor inducing the formation of hemophagocytic MGCs during L. donovani infection, functions of this protein in shaping the infection outcome in macrophages remain unclear. Here we evaluated the influence of upregulated ATP6V0D2 on intracellular survival of the parasites. L. donovani infection-induced hemophagocytosis of normal erythrocytes by macrophages was suppressed by RNAi-based knockdown of Atp6v0d2. The knockdown of Atp6v0d2 did not improve the survival of amastigotes within macrophages when the cells were cultured in the absence of erythrocytes. On the other hand, reduced intracellular survival of amastigotes in macrophages by the knockdown was observed when macrophages were supplemented with antibody-opsonized erythrocytes before infection. There, increase in cytosolic labile iron pool was observed in the L. donovani-infected knocked-down macrophages. It suggests that ATP6V0D2 plays roles not only in upregulation of hemophagocytosis but also in iron trafficking within L. donovani-infected macrophages. Superior access to iron in macrophages may be how the upregulated expression of the molecule brings benefit to Leishmania for their intracellular survival in the presence of erythrocytes.